PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAME TOURNAMET) UNTUK MENINGKATKAN KEAKTIFAN SISWA KELAS IV SDN BANJARSARI WETAN 01 DAGANGAN MADIUN MATA PELAJARAN IPAS - Adila Faaiza Alvi; Hendra Erik Rudyanto; Dera Suci Aprilia Sari (CV. ADIBA ASIHA AMIRA, 2024)
Student`s active learning create good learning. The purpose of this study was to increase student activity by using the Teams Game Tournament (TGT) type cooperative learning model for class IV science subjects at SDN Banjarsari Wetan 01 Dagangan Madiun. The subject in this research were 11 students of SDN Banjarsari Wetan 01 Dagangan Madiun, the procedure for implementation this classroom action research was carried out in a cyclicial form. The cycles consist of four stages namely planning, implementation, observation and reflection. This research uses a collaborative PTK type which consisted of two cycles, cycles I and cycles II. Data collection techniques uses observation, documentation and field notes. The instrumens used in this research were observation, documentation and field notes. The data analysis techniques used were descriptive qualitative and quantitativeThe resluted of this research showed that there was an improvement in the resulted of cycle I and I I using the cooperative learning model of teams game tournament type for science subject. The resulted of the first cycle of research show that students' activeness reached 79% this still does not showed appropriate resulted because there were indicators of oral activity that were not appropiate. Therefore, reflection and improvement were carried out in cycle I and cycle .Cycle II showed that students' activeness reached 85%.This shows that there is an increase in the percentage of students' activeness in each cycle. The results of this research show that student activity using the TGT method in learning science can increase student activity in carrying out learning activities